The Poetics of Place in the Novel of “Dimdim Castle” by the Writer (Arab Shamo) (Raparin Journal of Humanities (RJH), 2026)
This research, entitled "The Poetics of Place in the Novel 'Dimdim Castle' by Novelist Arab Shamo," is an attempt to demonstrate the strong relationship between place and man, and the reciprocal impact of different types of places. The poetics of place refers to the aesthetic and semantic characteristics produced within the novel, where the place is not merely a background but becomes a cultural and historical symbol that reflects a social and political reality. The research was conducted based on the principles of the structural-statistical method. From the very beginning of human life, a strong and powerful connection has existed between man and place. The place is the carrier of human experience, values, and meaning; it has an effect on the psyche and the determination of human identity. Among the most important findings of the research is that benefiting from the narrative techniques of foreshadowing and flashback, the description of places, and the expressive style with selected words and artistic images, creates beautiful scenes of "Dimdim Castle" through thought and imagination, embodying the life and authenticity of the place. It is worth mentioning that our research consists of two parts. The first part discusses the concept of poetics in general. The second part deals with the place, its types, and the extent of man's relationship with it.